Construction of a new dual-drug delivery system based on stimuli-responsive co-polymer functionalized D-mannose for chemotherapy of breast cancer. (20th April 2023) - Namazi, Hassan; Pooresmaeil, Malihe; Salehi, Roya
Graphical abstract: Highlights: CDs were prepared from ascorbic acid as a natural antioxidant raw material. A new stimuli-responsive photoluminescent CDs-poly(NIPAM-co-MAH)-D-Man nanocomposite was prepared via radical polymerization. CDs-poly(NIPAM-co-MAH)-D-Man was capable of loading both DOX and CUR drugs. The co-drug-loaded CDs-poly(NIPAM-co-MAH)-D-Man was pH and temperature-sensitive. The CDs-poly(NIPAM-co-MAH)-D-Man exhibited good biocompatibility. Abstract: In this work, we aimed to prepare the new blue-emissive carbon dots (CDs)-supported glyco-copolymer brushes functionalized D-mannose for targeted co-anticancer drug delivery to the breast cancer cells. Typically, the N-isopropyl acrylamide (NIPAM) and maleic anhydride (MAH) were copolymerized on the silica functionalized CDs surface via free-radical polymerization (CDs-poly(NIPAM-co-MAH)). Then, the synthesized CDs-poly(NIPAM-co-MAH) was functionalized with D-mannose (CDs-poly(NIPAM-co-MAH)-D-Man). The success of the nanocomposite synthesis was approved via several common characterization techniques. Thermal gravimetric analysis (TGA) analysis determined the percentage of polymer brush summed with D-mannose (D-Man) at about 12%. The size of CDs-poly(NIPAM-co-MAH)-D-Man was obtained at 30–42 nm. Photoluminescence (PL) analysis obtained an emission peak at ∼442 nm under the excitation wavelength of 365 for the nanocomposite, representing its blue luminescence nature. Doxorubicin (DOX) and curcumin (CUR) were co-loaded respectively, about ∼62% and ∼38% on CDs-poly(NIPAM-co-MAH)-D-Man (DOX@CUR@CDs-poly(NIPAM-co-MAH)-D-Man). The prepared system exhibited controlled drug release behavior and good biocompatibility in the in vitro cellular tests. The percentage of the arrested cells in sub G1 phase for the treated cells with DOX@CUR@CDs-poly(NIPAM-co-MAH)-D-Man was 100 %, while it was 86.85% for free DOX@CUR which can approve the high efficiency of DOX@CUR@CDs-poly(NIPAM-co-MAH)-D-Man in cancer therapy. Overall, the results displayed that the prepared nanocomposite can be potentially proposed as an efficient carrier for controlled and targeted anticancer drug delivery along with bioimaging.